The future of architecture in 100 buildings - Kushner, Marc, ....-; Krichels, Jennifer, ....- (New York : TED Books/Simon & Schuster, 2015)
The founder of Architizer.com and practicing architect draws on his unique position at the crossroads of architecture and social media to highlight 100 important buildings that embody the future of architecture.
"A TED original."
Keywords: Architecture, Modern -- 21st century